Assessing the role of visual dysfunctions in the association between visual symptomatology and the use of digital devices - Cacho-Martínez, Pilar; Cantó-Cerdán, Mario; Lara-Lacárcel, Francisco; García-Muñoz, Ángel (Journal of optometry, 2024)
To evaluate the association between visual symptoms and use of digital devices considering the presence of visual dysfunctions. An optometric examination was conducted in a clinical sample of 346 patients to diagnose any type of visual anomaly. Visual symptoms were collected using the validated SQVD questionnaire. A threshold of 6 hours per day was used to quantify the effects of digital device usage and patients were divided into two groups: under and above of 35 years old. A multivariate logistic regression was employed to investigate the association between digital device use and symptoms, with visual dysfunctions considered as a confounding variable. Crude and the adjusted odds ratio (OR) were calculated for each variable. 57.02 % of the subjects reported visual symptoms, and 65.02% exhibited some form of visual dysfunction. For patients under 35 years old, an association was found between having visual symptoms and digital device use (OR = 2.10, p = 0.01). However, after adjusting for visual dysfunctions, this association disappeared (OR = 1.44, p = 0.27) and the association was instead between symptoms and refractive dysfunction (OR = 6.52, p < 0.001), accommodative (OR = 10.47, p < 0.001), binocular (OR = 6.68, p < 0.001) and accommodative plus binocular dysfunctions (OR = 46.84, p < 0.001). Among patients over 35 years old, no association was found between symptoms and the use of digital devices (OR = 1.27, p = 0.49) but there was an association between symptoms and refractive dysfunction (OR = 3.54, p = 0.001). Visual symptoms are not dependent on the duration of digital device use but rather on the presence of any type of visual dysfunction: refractive, accommodative and/or binocular one, which should be diagnosed.